1996
DOI: 10.1111/j.1476-5381.1996.tb15505.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of bradycardic agent, S 16257, on ionic currents of rabbit sinoatrial node cells

Abstract: 1 The effect of the bradycardic agent S 16257 on the main ionic mechanisms of diastolic depolarization in sinoatrial node cells isolated from rabbit heart, was investigated by the patch-clamp technique in whole-cell and macro-patch recordings. 4 A high concentration of S 16257 (10 yM) had no detectable effect on T-type calcium current and slightly decreased L-type calcium current (-18.12+0.66%), without significant use-dependent blockade. 5 S 16257 had no effect on the delayed outward potassium current IK at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
238
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(277 citation statements)
references
References 13 publications
31
238
0
8
Order By: Relevance
“…Fitting the dose-response curve with the Hill equation yielded a half-block concentration of 1.5 M and a slope coefficient of 0.8. The concentration dependence of I f block was similar to that reported previously by Bois et al (1996).…”
Section: R E S U L T Ssupporting
confidence: 90%
See 2 more Smart Citations
“…Fitting the dose-response curve with the Hill equation yielded a half-block concentration of 1.5 M and a slope coefficient of 0.8. The concentration dependence of I f block was similar to that reported previously by Bois et al (1996).…”
Section: R E S U L T Ssupporting
confidence: 90%
“…A previous study has shown that ivabradine acts with a high degree of specificity on f-channels from the intracellular side of the membrane (Bois et al, 1996). We find that ivabradine blocks f-channels when they are open, and its block is strongly use-dependent.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…It is interesting to observe that in the mice treated orally with ivabradine for 1 week, reduction in HR was detectable with ivabradine plasma level in the range of 0.01-0.04 mM. In vitro patch-clamp studies showed that the IC 50 for the I f blockade by ivabradine is 1.5-2.2 mM (Bois et al, 1996;Thollon et al, 1997;Bucchi et al, 2002).…”
Section: X-j Du Et Almentioning
confidence: 98%
“…It has been shown that I f current of sinoatrial node pacemaker cells is affected by adrenergic stimulation (DiFrancesco & Tortora, 1991) and that ivabradine is a usedependent I f current blocker (Bois et al, 1996;Bucchi et al, 2002). Therefore, it is expected that the efficacy of ivabradine on HR would be modulated by alterations in the sympathetic activity.…”
Section: X-j Du Et Almentioning
confidence: 99%